Does presence of subclinical hypothyroidism and thyroid auto antibodies affect pregnancy outcomes in pregnancy? A record-based cross-sectional study - Ülkü Ayşe Türker Aras; Burcu Dinçgez (Elsevier, 2022)
Objective: Our aim in this study is to determine the relationship between TPOAb positivity and pregnancy outcomes in the subclinical hypothyroid patient group. Materials and methods: This study was started with 21,321 pregnant women, but after the exclusion criteria, 11,387 pregnant women were included int his study. Demographic characteristics of each patient group included in the study, such as age, bodymass index (BMI), and laboratory parameters such as complete blood count (hemogram), liver and kidney function tests, type of delivery, birth weight, neonatal intensive care admission, 1st and 5th minute APGAR scores, glucose tolerance test results, whether there was high blood pressure during pregnancy, whether there was premature rupture of membranes were recorded from the hospital information system and patient files. Results: Pregnant women with subclinical hypothyroidism were divided into groups according to their TPOAb status. When maternal and neonatal outcomes were evaluated between groups; Among these four groups there was a statistically significant difference only in impaired glucose tolerance (IGT) antibody groups with and without subclinical hypothyroidism according to their positivity (p < 0.01). When the euthyroid TPOAb negative group was taken as reference, the risk of impaired and TPOAb positive groups (OR: 1.210; 95% CI: 0.936-1.563; P = 0.145), impaired in the group with subclinical hypothyroidism but TPOAb positivity glucose tolerance 1.358(OR: 1.358); 95% CI: 1.042-1.770; P = 0.023) fold increased by 3.556 (OR: 3.556) in the group with subclinical hypothyroidism and TPOAb positivity; (95% CI: 2.37-5.343; p < 0,001). Conclusion: In ourstudy, there was a significant difference only in terms of IGT between the Groups with and without subclinical hypothyroidism, depending on whether they were positive for TPOAb or not. Therefore, studies in volving larger patient groups are needed.